2021
DOI: 10.1039/d0cp05069e
|View full text |Cite
|
Sign up to set email alerts
|

Thermal enhancement of upconversion emission in nanocrystals: a comprehensive summary

Abstract: Luminescence thermal stability is a major figure of merit of lanthanide-doped nanoparticles playing an essential role in determining their potential applications in advanced optics. Unfortunately, considering the intensification of multiple...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 149 publications
4
52
1
Order By: Relevance
“…However, currently, there are no available commercial systems able to tackle all the important parameters shown to affect the UCNPs' QY (e.g. excitation beam profile, scattering, and temperature [21][22][23] ). Several groups have measured the QY absolutely using integrating spheres, [24][25][26] and other groups have performed relative measurements using a material with known QY as a reference.…”
Section: Introductionmentioning
confidence: 99%
“…However, currently, there are no available commercial systems able to tackle all the important parameters shown to affect the UCNPs' QY (e.g. excitation beam profile, scattering, and temperature [21][22][23] ). Several groups have measured the QY absolutely using integrating spheres, [24][25][26] and other groups have performed relative measurements using a material with known QY as a reference.…”
Section: Introductionmentioning
confidence: 99%
“…The important role of water adsorption on the quenching of upconversion luminescence was demonstrated in many recent reports. 10,11,25 The adsorbed moisture provides non-radiative relaxation pathways for the populated excited levels of the lanthanide ions by transferring their energy to the stretching vibration of water molecules (∼3500 cm −1 ). 27 Vibrational overtones of OH-stretching were also pointed out for non-radiative relaxation.…”
Section: Thermal Cyclingmentioning
confidence: 99%
“…10 Based on carefully designed experiments and structural characterization by thermogravimetry (TGA) and Fourier-transform infrared spectroscopy (FTIR) the authors demonstrated that the intensity variations could be ascribed to the desorption of surface moisture at high temperatures (470 K), finding a 0.5% weight loss or gain on heating and cooling, respectively. Nevertheless, despite the extensive work on the subject, reviewed in a series of recent papers, [11][12][13] the real-time monitoring of the emissions during heating-cooling cycles has been disregarded. Only recently, Li and co-workers have briefly compared the thermally dependent UCL of oleic acid capped and uncapped UCNPs.…”
Section: Introductionmentioning
confidence: 99%
“…5 On the other hand, UCNPs suffer from the significant size-dependent luminescence efficiency decrease, 6 which compromises the functionality of UCNPs. Fortunately, the unique anomalous luminescence thermal enhancement recently discovered in UCNPs has been found to be size-dependent as well, 7–9 which initials great opportunities for applications such as optical thermal sensing and anti-counterfeiting. 10–15…”
Section: Introductionmentioning
confidence: 99%